Climate change : observed impacts on planet Earth - Letcher, T. M. (Trevor M.) (Amsterdam ; Boston : Elsevier, 2009)
Earth's climate is always changing. As the debate over the Earth's climate has grown, the term'climate change' has come to refer primarily to changes we've seen over recent years and those that are predicted to be coming, mainly as a result of human behavior. Climate Change: Observed Impacts on Planet Earth, Second Edition, serves as a broad, accessible guide to the science behind this often political and heated debate by providing scientific detail and evidence in language that is clear to both the climatologist and the non-specialist. The book contains 35 chapters on all scientific aspects of climate change, written by the world's authority of each particular subject. It collects the latest information on all of these topics in one volume. In this way, readers can make connections between the various topics covered in the book, leading to new ways of solving problems and looking at related issues. The book also contains major references and details for further research and understanding on all issues related to climate change, giving a clear indication of a looming crisis in global warming and climate change.
Possible causes of climate change: The role of atmospheric gases in global warming / R.P. Tuckett. The role of widespread surface solar radiation trends in climate change : dimming and brightening / S. Cohen. The role of space weather and cosmic ray effects in climate change / L.I. Dorman. The role of volcanic activity in climate and global change / G. Stenchikov. The role of variations of the earth's orbital characteristics in climate change / L.J. Lourens and E. Tuenter -- A geological history of climate change: A geological history of climate change / J. Zalasiewicz and M. Williams -- Indicators of climate and global change: Changes in the atmospheric circulation as indicator of climate change / T. Reichler. Weather pattern changes in the tropics and mid-latitudes as an indicator of global changes / R.M. Trigo and L. Gimeno. Bird ecology as an indicator of climate and global change / W. Fiedler. Mammal ecology as an indicator of climate change / M.M. Humphries. Climate change as temporal and spatial mismatches in insect communities / S.L. Pelini [and others]. Sea life (pelagic and planktonic ecosystems) as an indicator of climate and global change / M. Edwards. Changes in coral reef ecosystems as an indicator of climate and global change / M.J. Attrill. Changes in marine biodiversity as an indicator of climate change / B. Worm and H.K. Lotze. Intertidal indicators of climate and global change / N. Mieszkowska. Plant ecology as an indicator of climate and global change / M.D. Morecorft and S.A. Keith. The impact of climate and global change on crop production / G.R. Dixon. Rising sea levels as an indicator of global change / R. Gehrels. Sea temperature change as an indicator of global change / M.J. Attrill. Ocean current changes as an indicator of global change / T. Kanzow and M. Visbeck. Ocean acidification as an indicator of climate change / C. Turley and H.S. Findlay. Ice sheets : indicators and instruments of climate change / D.G. Vaughan. Lichens as an indicator of climate and global change / A. Aptroot. Coastline degradation as an indicator of global change / R.J. Nicholls, C. Woodroffe and V. Burkett. Plant pathogens as indicators of climate change / K.A. Garrett [and others].
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Climatic changes; Global environmental change; Climatic changes; Global environmental change; Klima$1-W[(Bderung.s; Anthropogene Klima$1-W[(Bderung.s; Umweltver$1-W[(Bderung.s; Umweltindikator; Klima$1-W[(Bderung.s; Aufsatzsammlung; Electronic books